The Effectiveness Of Cooperative Learning Type Team Assisted Individualization Based On Constructivism Toward Ability To Think Mathematically Creative Of Student - Dwi Sulistyaningsih; Venissa Dian Mawarsari (Universitas Muhammadiyah Semarang, 2016)
Abstract. Many students have difficulty and get low score in trigonometry. Some reason said this subject contains a lotof formulas and the teachers have not used the learning system that can make students more active. This study aims to determine the effectiveness of the implementation of cooperative learning type Team Assisted Individualization (TAI)based on constructivism towad students' ability to think trigonometry creatively. This study is an experimental studyconducted at SMA Muhammadiyah 1 Semarang. Data collection technique is student activity observation and creativethinking ability tests of mathematical ability. The result shows classical completeness of creative thinking abilities ofstudents reached 85.7%. Value of creative mathematical thinking skills (KBKM) was influenced by students' activity was78.4% and the value of Mathematical Creative Thinking Skills test experimental class was better than the control class. Itmeans that learning of mathematics trigonometry by applying the cooperative model type TAI constructivism based ismore effective than learning by using conventional learning models.